Agro-morphological and nutritional Characterization of horned melon Accessions from selected agro-ecological Zones in kenya - Owino, Marline Hanny (University of Embu, 2020)
African horned melon (Cucumis metuliferus) is an indigenous crop belonging to the family Cucurbitaceae. The crop has been neglected despite its high potential. Therefore, to conserve the biodiversity of this crop, there is need to promote its domestication and production. However, this can only be realized if its morphology, agronomic and nutritional value is understood. The objective of this study was to determine the agromorphological performance and nutritional composition of horned melon accessions obtained from selected agro-ecological zones in Kenya. The study was conducted at the University of Embu research farm for two cropping seasons; October to January 2018 and March to June 2019. The experiment was laid out in a randomized complete block design with nineteen accessions replicated three times. The accessions were planted in experimental plots measuring 3m x 3m at a spacing of 1m by 1m. Morphological and agronomic characterization was based on modified International Plant Genetic Resource Institute (IPGRI) descriptors for melon. Data was recorded from four plants per plot per replicate. The fruit content of Fe and P were determined using atomic absorption spectrophotometry while Na and K were determined using flame photometry procedure. Vitamin C content was estimated by titrimetric method. Sugar content was determined using a brix refractometer. The qualitative and quantitative data obtained from morphological and agronomic characters were organized in a matrix and subjected to cluster analysis. A dendrogram was then constructed using unweighted pair-group method with arithmetic average. Agronomic and nutritional data was also subjected to analysis of variance using XLSTAT 2019 statistical software and means separated using Students Newmans Keuls test at 95% level of confidence. Significant differences (p<0.05) were observed in all the quantitative traits except the number of branches and main vine length. However, qualitative variations were only observed in fruit shape, rind colour and seed shape. In both seasons, the dendrogram separated into 5 supported clusters with the diversity between classes being 63.82% in the first season and 68.84% in the second season and diversity within classes being 36.18% in the first season and 31.16% in the second season. Accessions from Rongo, Wote, Siakago, Maragua, Oyugis and Meru had the highest fruit number and fruit weight for both season hence they can be more preferred by farmers and consumers. The accessions also varied significantly (p<0.05) in their nutritional composition except the Moisture Content and the Vitamin C. The composition of the mineral contents in the fruits followed the order K > P >Na >Fe .Potassium (K) content ranged from 249.52mg/100g-165.17mg/100g for Kangundo and Embu accessions respectively. Sodium (Na) ranged from 2.27mg/100g- 1.10mg/100g for Mitunguu and Siakago accessions respectively. Phosphorus (P) range was 40.49mg/100g8.76mg/100g for Migori and Machakos accessions respectively. Iron (Fe) ranged from 2.61mg/100g-0.80mg/100g for Kianjokoma and Maragua accessions respectively. The horned melon accessions tested in this study showed a high agro-morphological and nutrition variation. The study recommended the accessions from Kehancha, Embu and Siakago which recorded highest sugar content across seasons to be used by plant breedersto improve on taste which is considered to be bland by some consumers.
Keywords: Melon